Exploring the Antitumor Efficacy of PEGylated Liposomes Loaded with Licorice Extract for Cancer Therapy - Haghighat, Zeinab Azizi; Safekordi, Aliakbar; Ardjmand, Mehdi; Akbarzadeh, Azim (Current Cancer Drug Targets, 2025)
BackgroundGlycyrrhizic Acid (GA), a compound derived from licorice, has exhibited promising anticancer properties against several cancer types, including Prostate Cancer (PCa) and Gastric Cancer (GCa).ObjectiveThis study has introduced a novel approach involving the encapsulation of GA and Licorice extract (Lic) into Polyethylene Glycol Liposomes (PEG-Lip) and assessed their efficacy against AGS (human gastric cancer) and PC-3 (human prostate cancer) cells, marking the first report of this endeavor.MethodsWe synthesized GA-loaded PEG-Lip (GA PEG-Lip) and Lic-loaded PEG-Lip (Lic PEG-Lip) through the reverse-phase evaporation method.ResultsCharacterization of these liposomal formulations revealed their size, drug encapsulation, and loading efficiencies to be 110 ± 2.05 nm, 117 ± 1.24 nm; 61 ± 0.81%, 34 ± 0.47%; and 8 ± 0.41% and 4.6 ± 0.21%, respectively. Importantly, the process has retained the chemical structure of both GA and Lic. Furthermore, GA and Lic have been released from the PEG-Lip formulations in a controlled manner.In our experiments, both nanoformulations exhibited enhanced cytotoxic effects against AGS and PC-3 cells. Notably, GA PEG-Lip outperformed Lic PEG-Lip, reducing the viability of PC-3 and AGS cells by 12.5% and 15.9%, respectively.ConclusionThese results have been corroborated by apoptosis assays, which have demonstrated GA PEG-Lip and Lic PEG-Lip to induce stronger apoptotic effects compared to free GA and Lic on both PC-3 and AGS cells.This study has underscored the potential of encapsulating GA and Lic in PEG-Lip as a promising strategy to augment their anticancer efficacy against prostate and gastric cancers.
Keywords: PEGylated liposome